Organizational ethical self-identity precautionary model / Norazamina Mohamed ... [et al.] - Mohamed, Norazamina; Yaacob, Najihah Marha; Abdullah, Azizah; Ahmad, Suraya (2018)
This research develops an Organizational Ethical Self-Identity Precautionary Model in sustaining the quality life of public that integrates concepts of ethical leadership, ethical employees, spirituality encouragement, spirituality acceptance and ethical guidelines. The National Principles of Malaysia, the Federal Constitution together with the institutions such as Malaysian Institute of Integrity and Anti-Corruption Agency Malaysia are to ensure organizations and their members behave in integrity manner with no corruption and no violations of public right. However, cases such as fraud, bribery and corruption continued to occur. They caused huge financial losses and in fact bring bad image to the organizations and Malaysia. These blunders have made public question the effectiveness of available regulations in preventing such crimes. Therefore, initial precaution efforts in preventing crime and corruption should start from the organizational level by inculcating sound ethical practices. Thus, the objectives of this study are (a) to explore the integrated concepts of ethical leadership, ethical employees, spirituality encouragement, spirituality acceptance and ethical guidelines in enhancing the quality of public life and (b) to propose an organizational ethical self-identity precautionary model in sustaining quality of public life. Mixed methodology was applied by initially focus on qualitative method, interview and observations of the respondents in the government agencies by using criterion purposive sampling. This was then supported by questionnaires survey using stratified and systematic sampling. Results from qualitative analysis highlight detailed attributes for the five elements suggested in Organizational Ethical Self-Identity Precautionary Model (OESP). Eight (8) ethical leadership attributes, nine (9) ethical employees’ attributes, six (6) spirituality encouragement attributes, six (6) spirituality acceptance attributes and five (5) ethical guidelines attributes were identified. These attributes were then confirmed by nineteen (19) reflective questions of ethical leadership, fourteen (14) reflective questions of ethical employees, six (6) reflective questions of spirituality encouragement, six (6) spirituality acceptance and nineteen (19) reflective questions of ethical guidelines using quantitative analysis. This new model is very much relevant to the government's aspiration in the National Key Result Areas (NKRAs). This model is expected to support the Ministry of Home Affairs in reducing crime and the Prime Minister's Department in fighting the corruption. In a long term, the model will enhance quality of physical wellbeing, material wellbeing, social wellbeing and emotional wellbeing of the public. These identified attributes should become the ethical identity and ethical direction of Malaysian Public Sector Agencies in enhancing its ethical accountability. It should further improve the trust among Malaysian and the international community towards the governance of Malaysian Public Sector Agencies.